1987
DOI: 10.1128/jcm.25.1.133-137.1987
|View full text |Cite
|
Sign up to set email alerts
|

Antigenuria in infants with acute and congenital Chagas' disease

Abstract: Detection and partial characterization of Trypanosoma cruzi soluble antigens (SAg) in urine, as well as demonstration of parasite circulating antigens (CAg) in serum from pediatric patients with acute (10 patients) and congenital (10 patients) Chagas' disease, are reported. Classical techniques for parasite detection and antibody serology were also conducted in both groups. Samples collected before the onset of parasiticidal drug treatment were tested by an enzyme-linked immunosorbent assay for SAg and CAg dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…The crossing of T. cruzi to urine in experimentally infected mice is apparently independent of renal injuries [189]. The presence of DNA in urine is associated with the presence of parasite DNA in blood and heart and with a high level of parasite DNA in blood, but not with the presence of parasites in kidney or kidney injury [189][190][191]. The detection of antigens within the urine of patients suffering from acute [192] or chronic CD [193] has opened up some new innovative approaches for diagnosis.…”
Section: Urinementioning
confidence: 99%
“…The crossing of T. cruzi to urine in experimentally infected mice is apparently independent of renal injuries [189]. The presence of DNA in urine is associated with the presence of parasite DNA in blood and heart and with a high level of parasite DNA in blood, but not with the presence of parasites in kidney or kidney injury [189][190][191]. The detection of antigens within the urine of patients suffering from acute [192] or chronic CD [193] has opened up some new innovative approaches for diagnosis.…”
Section: Urinementioning
confidence: 99%
“…The utility of parasite antigen detection in urine has also been studied. It has been demonstrated that T. cruzi antigens can readily be detected in urine from patients with acute Chagas' disease (87), but more recent work suggests that this method will not be useful for diagnosis of patients with chronic T. cruzi infection (116).…”
Section: Diagnosismentioning
confidence: 99%
“…Out of the 147 chronic chagasic patients, 26 presented clinical symptoms of cardiac disease, two showed gastrointestinal lesions and 14 patients were in the indeterminate phase of the disease. Acute and congenital chagasic sera (n=76) were obtained from patients with patent parasitaemia and clinical manifestations of acute infection detected 15 to 80 days before blood collection (Luquetti et al 1986, Freilij et al 1987. These sera were also collected before treatment.…”
Section: Introductionmentioning
confidence: 99%